The Role of Community Service in Promoting Social Inclusion and Reducing Socio-Economic Inequality - Purba, Jan Horas Veryady; Khim, Soei; Nurisnaini, Neni (PT. LITERASI SAINS NUSANTARA, 2026)
Community service is a strategic instrument in promoting social inclusion and reducing socio-economic inequality, particularly amid the complex development challenges faced by contemporary societies. This study aims to expand and enrich scholarly references concerning the role of community service in supporting inclusive social development. The research employs a literature review method with a qualitative approach and descriptive analysis. Data were collected from Google Scholar and selected credible websites, covering publications from 2016 to 2026. From an initial pool of 50 identified articles, a rigorous selection process based on relevance and quality resulted in 32 articles used as the main sources of analysis. The findings indicate that community service programs grounded in empowerment, participation, and sustainability significantly contribute to enhancing social inclusion, strengthening social capital, and reducing socio-economic inequality. Furthermore, synergy among universities, communities, and other stakeholders emerges as a key factor in the success of community service initiatives. This study underscores the importance of strengthening the design, implementation, and evaluation of community service programs to ensure more measurable and long-term impacts.